P53, KI-67, CD117 expression in gastrointestinal and pancreatic neuroendocrine tumours and evaluation of their correlation with clinicopathological and prognostic parameters - Kımıloğlu Şahan, Elife; Erdoğan, Nusret; Ulusoy, İlknur and Samet, Ergün and Akyıldız İğdem, Ayşenur and Gönüllü, Doğan (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Gastrointestinal and pancreatic neuroendocrine tumors (GEPNETs) originate from the cells of the endocrine system. Their molecular genetic mechanism of development and progression is complex and remains largely unknown. The purpose of this study was to review the gastrointestinal and pancreatic neuroendocrine tumors and to evaluate p53, Ki-67 and CD 117 expressions with their clinicopathological correlations. Materials and Methods: Twenty-one patients were reviewed and classified as having well-differentiated neuroendocrine neoplasm (WDET, Grade I), well-differentiated neuroendocrine carcinoma (WDEC, Grade II) and poorly differentiated neuroendocrine carcinoma (PDEC, Grade III). We performed immunohistochemical tests to characterize the expession of the immunoreactivity for synaptophysin, chromogranin, p53, Ki67 and CD 117. Results: Median age of 21 patients was 43 years. Thirteen (61.9%) patients were male and eight (38.1%) patients were female. Tumors were located in the stomach (38.1%), appendix (38.1%), duodenum (4.8%), ileum (4.8%), colon (9.5%), and pancreas (4.8%). Conclusion: There was a statistically significant difference between well-differentiated endocrine neoplasm (Grade I), and well-differentiated endocrine carcinoma (WDEC, Grade II) and PDEC for Ki-67 >20% (p<0.001) (Pearson chi-square test). There was a statistically significant difference between WDET (Grade I), WDEC (Grade II) and PDEC (Grade III) for p53 positivity (p<0.05) (Pearson chi-square test).